2021
DOI: 10.4274/jtgga.galenos.2021.2020.0228
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal uterine bleeding types according to the PALM-COEIN FIGO classification in a medically underserved American community

Abstract: Objective: To describe the distribution of abnormal uterine bleeding (AUB) type according to the polyp (AUB-P); adenomyosis (AUB-A); leiomyoma (AUB-L); malignancy and hyperplasia (AUB-M); coagulopathy (AUB-C); ovulatory dysfunction (AUB-O); endometrial (AUB-E); iatrogenic (AUB-I); and not yet classified International Federation of Gynecology and Obstetrics classification system in a medically underserved American inner-city population. Our secondary objective was to find an association between ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
(33 reference statements)
2
13
0
Order By: Relevance
“…Several studies have reported a prevalence rate of AUB-P fluctuated from 6.7% to 26.5%. [6][7][8][9]16 Our results were somewhere in their middle range and were very close to what Yu Sun et al 17 reported. Polyps are epithelial proliferations arising from the endometrial stroma and glands.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Several studies have reported a prevalence rate of AUB-P fluctuated from 6.7% to 26.5%. [6][7][8][9]16 Our results were somewhere in their middle range and were very close to what Yu Sun et al 17 reported. Polyps are epithelial proliferations arising from the endometrial stroma and glands.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of AUB‐P, AUB‐A, and AUB‐M in our study was 16.53%, 9.58%, and 2.91%, respectively. Several studies have reported a prevalence rate of AUB‐P fluctuated from 6.7% to 26.5% 6–9,16 . Our results were somewhere in their middle range and were very close to what Yu Sun et al 17 reported.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The nonstructural ones mainly include the anovulatory type which is associated with ovulation, or with ovulatory menstrual disorders, and the AUB caused by the contraceptive ring or subepithelial implants. Iatrogenic AUB is mostly caused by improper medication and some AUB of unknown cause [ 18 ]. Endometrial polyps, which causes uterine bleeding, is a common uterine cavity lesion with abnormal growth and excessive thickening of the endometrium due to some reasons.…”
Section: Discussionmentioning
confidence: 99%